SYNTHESIS AND CHARACTERIZATION OF POLY(URETHANE-b-ACRYLATE) BLOCK COPOLYMERS BY USING MACROAZOINITIATORS - Deniz, Sennur (YILDIZ TECHNICAL UNIV, 2005)
The block copolymers of poly(urethane-b-acrylate) (PUA)s were synthesized by the radical solution polymerization with polyurethane based macroazoinitiators (PUMAIs), and butyl methacrylate (n-BMA) or 2-hydroxyethyl methacrylate (HEMA). The PUMAI synthesis is carried out with using poly(ethylene glycol) s (PEG) having different number average molecular weights ((M) over bar (n) = 400 and 1500 g/mol) as a soft segment and 2,4-toluene diisocyanate (TDI) or 1,6-hexamethylene diisocyanate (HMDI) as a hard segment. These macroazoinitiators vary in the molecular weight of soft-segment and type of hard-segment with all having constant amount of hard-segment. The number average molecular weights of PUMAIs were measured by the method of dibutylamine-back titration (ASTM D 2572) as a range of 2150-7700 g/mol. The number average molecular weights of PUA copolymers were determined by gel permeation chromatography (GPC). It was found that the number average molecular weights of PUA copolymers obtained with n-BMA were between 10100-14600 g/mol with a polydispersity of 1.78-2.12. The effects of the hard-segment type and the molecular weight of soft-segment on the properties of PUA copolymers were investigated. It was observed that the molecular weights of PUA copolymers increase with increasing the molecular weight of PEG used in PUMAI synthesis.
Keywords: Poly(urethane-b-acrylate); macroazoinitiator; n-butyl methacrylate; 2-hydroxyethyl methacrylate; Engineering